Synthesis and Identification of New Oxazepine Derivatives bearing Azo group in their structures - Sallal, Zainab Amer; Ghanem, Hasan Thamer (Iraqi Journal of Science, 2018)
In this contribution new oxazepine compounds containing azo group were preppared. In the firststep,4-(dimethylamino)-3-((4-methoxy phenyl) diazenyl) benzaldehyde [Z] was synthesised by using 4-methoxyaniline. The second step was the condensation reaction between aldehyde group of the azo compound [Z] anddifferent primary aromatic amines [4-hydroxyaniline, 4-chloroaniline and 4-amino- N-(pyrimidin-2-yl) benzenesulfonamide] to yield new azo Schiff bases compounds [A1-A3] respectively. In the final step, oxazepine compounds [B1-B3] and [B4-B6] were prepared from reaction imines compounds [A1-A3] with maleic anhydride and phathalic anhydride in dry benzene respectively. All these derivatives were characterized by melting points and FTIR spectroscopy, some of them were characterized by 1H-NMR spectroscopy.